Automatic water irrigation - Ishak, Muhamad Hamzi; Mohd Sharil, Basyir (2016)
Automatic water irrigation is design to create something that help in plantation. Irrigate or it other name is moisten is a system about the detection of moisture. Irrigate also indicate as sprinkler that is a sprinkler that watered plantation. Automatic means it will function without the human helps. The sensor will be the main input for this system. The main aim is to create a system that will function without the presences of human. So when the moisture of soil is dry, the system will automatically ON and the water pump will sprinkle the water into the soil. It will not be function if the soil in wet condition, so it can prevent from using a lot of water. This project also will reducing from using man power to closed the pipe, so it is advantages for the farmers to make sure that their plantation will get enough water.